Low-Frequency Noise Due to Iron Impurity Centers in GaN-Based HEMTs - Fleetwood, Daniel M.; Li, Xun; Zhang, En Xia; Schrimpf, Ronald D.; Pantelides, Sokrates T. (IEEE transactions on electron devices, 2024)
Commercial Schottky-gate AlGaN/GaN high-electron-mobility transistors (HEMTs) exhibit a large peak in low-frequency (LF) noise magnitude at \sim 325 K. An activation energy of 0.56 ± 0.05 eV is determined for the responsible generation-recombination (G-R) center via Arrhenius analysis. Comparisons with first-principles calculations and complementary experimental studies show that this G-R center is due to substitutional iron impurities, Fe _{\text{Ga}} . Independent determination of the activation energy for this prominent noise peak enables recalibration of the Dutta-Horn model of LF noise for GaN-based HEMTs and a downward revision by \sim 20% of past LF-noise estimates of effective defect energies. The resulting LF-noise-derived defect-energy distributions are consistent with deep-level-transient spectroscopy (DLTS) measurements on GaN-based diodes before and after 1.8-MeV proton irradiation. The activation of Fe _{\text{Ga}} -related centers via defect dehydrogenation during high-voltage stress is demonstrated via LF noise measurements on AlGaN/GaN-on-SiC HEMTs.